Association Between Time to Colonoscopy After a Positive Fecal Test Result and Risk of Colorectal Cancer and Cancer Stage at Diagnosis - Corley, Douglas A; Jensen, Christopher D; Quinn, Virginia P; Doubeni, Chyke A; Zauber, Ann G; Lee, Jeffrey K; Schottinger, Joanne E; Marks, Amy R; Zhao, Wei K; Ghai, Nirupa R; Lee, Alexander T; Contreras, Richard; et al. (JAMA : the journal of the American Medical Association, 2017)
The fecal immunochemical test (FIT) is commonly used for colorectal cancer screening and positive test results require follow-up colonoscopy. However, follow-up intervals vary, which may result in neoplastic progression. To evaluate time to colonoscopy after a positive FIT result and its association with risk of colorectal cancer and advanced-stage disease at diagnosis. Retrospective cohort study (January 1, 2010-December 31, 2014) within Kaiser Permanente Northern and Southern California. Participants were 70 124 patients aged 50 through 70 years eligible for colorectal cancer screening with a positive FIT result who had a follow-up colonoscopy. Time (days) to colonoscopy after a positive FIT result. Risk of any colorectal cancer and advanced-stage disease (defined as stage III and IV cancer). Odds ratios (ORs) and 95% CIs were adjusted for patient demographics and baseline risk factors. Of the 70 124 patients with positive FIT results (median age, 61 years [IQR, 55-67 years]; men, 52.7%), there were 2191 cases of any colorectal cancer and 601 cases of advanced-stage disease diagnosed. Compared with colonoscopy follow-up within 8 to 30 days (n = 27 176), there were no significant differences between follow-up at 2 months (n = 24 644), 3 months (n = 8666), 4 to 6 months (n = 5251), or 7 to 9 months (n = 1335) for risk of any colorectal cancer (cases per 1000 patients: 8-30 days, 30; 2 months, 28; 3 months, 31; 4-6 months, 31; and 7-9 months, 43) or advanced-stage disease (cases per 1000 patients: 8-30 days, 8; 2 months, 7; 3 months, 7; 4-6 months, 9; and 7-9 months, 13). Risks were significantly higher for examinations at 10 to 12 months (n = 748) for any colorectal cancer (OR, 1.48 [95% CI, 1.05-2.08]; 49 cases per 1000 patients) and advanced-stage disease (OR, 1.97 [95% CI, 1.14-3.42]; 19 cases per 1000 patients) and more than 12 months (n = 747) for any colorectal cancer (OR, 2.25 [95% CI, 1.89-2.68]; 76 cases per 1000 patients) and advanced-stage disease (OR, 3.22 [95% CI, 2.44-4.25]; 31 cases per 1000 patients). Among patients with a positive fecal immunochemical test result, compared with follow-up colonoscopy at 8 to 30 days, follow-up after 10 months was associated with a higher risk of colorectal cancer and more advanced-stage disease at the time of diagnosis. Further research is needed to assess whether this relationship is causal.